2020
DOI: 10.1101/2020.04.07.030684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The aging transcriptome and cellular landscape of the human lung in relation to SARS-CoV-2

Abstract: Since the emergence of SARS-CoV-2 in December 2019, Coronavirus Disease-2019 (COVID-19) has rapidly spread across the globe. Epidemiologic studies have demonstrated that age is one of the strongest risk factors influencing the morbidity and mortality of COVID-19. Here, we interrogate the transcriptional features and cellular landscapes of the aging human lung through integrative analysis of bulk and single-cell transcriptomics. By intersecting these age-associated changes with experimental data on host inte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 75 publications
5
32
0
Order By: Relevance
“…However, the number of patients increases significantly with increasing age [52], which is consistent with the general observation of a less severe disease in children. It has been reported that the expression of host cell entry proteins like ACE2 and TMPRSS2 does not increase with age and cannot explain a more severe disease in the elderly [53]. Different risk factors have been proposed to contribute to the increase in severity of the disease due to ageing [53–55].…”
Section: Discussion and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, the number of patients increases significantly with increasing age [52], which is consistent with the general observation of a less severe disease in children. It has been reported that the expression of host cell entry proteins like ACE2 and TMPRSS2 does not increase with age and cannot explain a more severe disease in the elderly [53]. Different risk factors have been proposed to contribute to the increase in severity of the disease due to ageing [53–55].…”
Section: Discussion and Hypothesismentioning
confidence: 99%
“…It has been reported that the expression of host cell entry proteins like ACE2 and TMPRSS2 does not increase with age and cannot explain a more severe disease in the elderly [53]. Different risk factors have been proposed to contribute to the increase in severity of the disease due to ageing [53–55]. Some of these risk factors are higher expression of genes associated with cell adhesion and oxytocin signalling, lower expression of genes involved in mitochondrial translation and mitosis, decrease in total alveolar macrophages, immunosenescence and metabolic diseases.…”
Section: Discussion and Hypothesismentioning
confidence: 99%
“…Given that age is a major risk factor for COVID-19 severity, we explored whether the expression of these differentially expressed genes may naturally change with age [25]. We analyzed the differentially expressed genes between infected and bystander ciliated cells for previously determined age-associated genes ( Figure 5D) [26]. Age-associated genes were significantly enriched among the differently expressed genes ( Figure 5E).…”
Section: Differentially Expressed Genes In Response To Sars-cov-2 Infmentioning
confidence: 99%
“…Paradoxically, healthy lung tissues as a whole show only modest expression for either ACE2 and TMPRSS2, which is readily apparent in a number of expression databases and widely available resources such as GTEx ( Figure S4). Nonetheless, a number of studies mining scRNA-seq data reported marked expression of ACE2 and/or TMPRSS2 in a specific lung cell population called alveolar type II (AT2) cells (Chow and Chen, 2020;Travaglini et al, 2019;Zhao et al, 2020). However, these observations have been challenged by more recent studies.…”
Section: Respiratory Tract: How Does Sars-cov-2 Infect Lung Cells?mentioning
confidence: 99%
“…It is made available under a The copyright holder for this preprint (which this version posted May 17, 2020. . https://doi.org/10.1101/2020.05.08.084806 doi: bioRxiv preprint TMPRSS2 expression levels tend to mildly decrease with age in human lung tissue (Chow and Chen, 2020). We found that neither ACE2 nor TMPRSS2/4 on their own were differentially expressed between young and old nasal epithelia, but we observed that the percentage of ACE2 + TMPRSS2 + /4 + double-positive cells was significantly greater in older donors, both within ciliated and secretory cells.…”
Section: Nasal Epithelium: Niche or Battleground?mentioning
confidence: 99%